EXAMINING THE IMPACT MANAGERIAL OWNERSHIP AND FINANCIAL PERFORMANCE ON DIVIDEND POLICY - Aris Munandar; Siti Fatimah; Pandu Adi Cakranegara; Asri Kunda; PA. Andiena Nindya Putri (Jurnal Ekonomi, 2023)
Financial performance is a depiction of the company's financial demands throughout a given time period in terms of raising and disbursing funds. These requirements are often defined by indices of capital sufficiency, liquidity, and profitability. Monetary execution is a vision of obtaining organizational prosperity that may be expressed as what will happen that has been reached for the various exercises that have been carried out. The method utilized in this article is a qualitative method that incorporates a literature review or library research. The purpose of this article is to compare existing hypotheses to older theories in the research literature. The literature used is material from study findings or reviews reported in scientific publications in national and international forms related to financial management. All of the publications included were found using Mendeley's electronic data literacy search engine and Google Scholar. Based on the analysis of the impact of managerial ownership and financial performance on dividend policy, it is feasible to conclude that (1) managerial ownership has a significant impact on dividend policy in firms. (2) Financial performance has a significant impact on a company's dividend policy.